Pengembangan Modul Ajar dengan Memadukan Technological Pedagogical Content Knowledge (TPACK) untuk Meningkatkan Domain Pengetahuan Peserta Didik Kelas IV SD - Sobari, Ahmad; Chan, Faizal; Budiono, Hendra (Universitas Batanghari Jambi, 2024)
This research aims to develop a teaching module by combining Technological Pedagogical Content Knowledge (TPACK) to increase the knowledge domain of fourth grade elementary school students and to determine the feasibility of a teaching module by combining Technological Pedagogical Content Knowledge (TPACK) to increase the knowledge domain of fourth grade elementary school students . The development model used in this research is the ADDIE (Analyze, Design, Development, Implementation, Evaluate) development model. The results of this research show that the development of teaching modules by combining Technological Pedagogical Content Knowledge (TPACK) to improve the overall knowledge domain of fourth grade elementary school students can be used during the learning process at school.